Wondershare Quiz Creator لتقويم تعليم مهارة القراءة - Harun, Uhame Binti (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2019)
Advances in technology and information have a positive impact on the world of education. One of the impacts is to make it easier for teachers to make learning media and learning evaluation. Evaluation is used to measure the ability of students, to determine the extent to which the material has been mastered and learning objectives have been achieved. Many applications have been developed for learning evaluation, one of which is the Wondershare Quiz Creator. Wondershare Quiz Creator is a test maker application that is easy for teachers and interesting for students. This study uses the Research and Development Method 4D Model with a qualitative approach. The 4D Research Method consists of: Define, Design, Develop, and Disseminate but researchers limit this method to develop because of limited time and costs. Sources of data are collected from textbooks, and results from validator questionnaires. The results of this study are the tests used in the evaluation of Arabic learning based on Wondershare Quiz Creator for class XI, with five types of question models, namely: True False, Matching, Multiple Choice, Word Bank and Click Map. With this application, it is expected to be able to increase teacher creativity in making learning tests so that they become more interesting and also update technology-based learning evaluation tools.